Design and development of multimedia learning module on circular motion - Mohamed Yasin, Farha (2016)
Science and technology has improved a great impact in all aspects of life particularly in education. Various latest multimedia technology was introduced to the world. Multimedia technology is a perfect platform used in teaching and learning (T&L). The study was focused on developing a multimedia learning module of Circular Motion to assist student’s understandings of correct physics concepts. This module was developed based on the ADDIE model by using I-Spring Presenter as a delivery platform. The evaluation process is to get the students’ feedback on their understanding of the subject matter and their perception towards the multimedia learning module that has been developed. A total of sixty students in the Bachelor of Science program at the University Putra Malaysia who took Physics I and General Physics courses were selected as respondents. A set of questionnaire was used as the instrument for this study. The data findings were analyzed using mean scores for quantitative data and for the qualitative data, which are comments and suggestions were evaluated using thematic analysis approach. The study indicates that the respondents are satisfied with the multimedia learning module, where the overall average mean score is 3.41. Post test results have shown an improvement in the students' understanding and have reduced the misconceptions of circular motion. This module was expected to be used as a reference material for the students to promote the effective learning and to provide a guideline for educators in enhancing teaching effect. Some improvements still need to be done, especially in terms of audio settings to ensure learning through multimedia module can be effectively implemented.